Optimal analysis for segmented flux switching machine in the more electric engine insulation lifetime monitoring for motor windings - Devipriya (2019)
A comprehensive review is done to monitor the remaining insulation lifetime of the machine windings. This paper has looked into a specific type of segmented flux switching machine to track the insulation lifetime. There are many co-related reasons for the insulation of a machine winding to fail. Therefore, an in-depth research on the different stresses contributing to the failure of insulation failure have been done. Since, this project is purely based on simulation, there will be more emphasis shown to the impact that electrical stress has on the insulation lifetime. Therefore, a machine was created based on a simple application of a pump. The machine was both simulated in normal operating condition and in a faulty condition. The machine was forced to fail with an inter-turn fault in one of its phases. With both the simulation results, an analysis will be proposed to carry out with a mathematical model for electrical stress. This will be one major contribution from the stresses to the breakdown of the winding insulation.